Specific metabolomics adaptations define a differential regional vulnerability in the adult human cerebral cortex - Cabré, Rosanna; Jové, Mariona; Naudí, Alba; Ayala, Victoria; Piñol-Ripoll, Gerard; Gil-Villar, Maria Pilar; Dominguez-Gonzalez, Mayelin; Obis, Èlia; Berdun, Rebeca; Mota-Martorell, Natàlia; Portero-Otín, Manuel; Ferrer, Isidre; et al. (Frontiers in Molecular Neuroscience, 2016)
Brain neurons offer diverse responses to stresses and detrimental factors during development and aging, and as a result of both neurodegenerative and neuropsychiatric disorders. This multiplicity of responses can be ascribed to the great diversity among neuronal populations. Here we have determined the metabolomic profile of three healthy adult human brain regions—entorhinal cortex, hippocampus, and frontal cortex—using mass spectrometry-based technologies. Our results show the existence of a lessened energy demand, mitochondrial stress, and lower one-carbon metabolism (particularly restricted to the methionine cycle) specifically in frontal cortex. These findings, along with the better antioxidant capacity and lower mTOR signaling also seen in frontal cortex, suggest that this brain region is especially resistant to stress compared to the entorhinal cortex and hippocampus, which are more vulnerable regions. Globally, our results show the presence of specific metabolomics adaptations in three mature, healthy human brain regions, confirming the existence of cross-regional differences in cell vulnerability in the human cerebral cortex.